“Cheating, No Matter How You Try to Dress It up”. Newspaper Coverage of Polyamory, 1994–2023 - Alon Lischinsky (Open Gender Journal)
Polyamorous relationships face considerable disadvantages in contemporary Western societies, from lack of legal recognition to pervasive prejudice and stigma. While many scholars have pointed out the role of mainstream media in reproducing this prejudice, we still lack a general overview of the nature and evolution of newspaper coverage of polyamory. In this article, I use corpus linguistic techniques to identify and categorise the characteristic vocabulary of a corpus of articles representing English-language coverage of polyamory in global mainstream newspapers from 1994 to 2023. The analysis shows that coverage tends to concentrate on issues of sexuality; on experiences of jealousy; and on negative ethical judgements. Terminology reflecting the views and principles of the polyamorous community is rare in comparison. The article is accompanied by the dataset and code to facilitate verification, replication and extension of this research.